PENGARUH PENGELOLAAN KEUANGAN DAERAH DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KINERJA PEMERINTAH DAERAH (Studi Empiris Pada Organisasi Perangkat Daerah Kota Jayapura) - Stevani Veronica M. Ireeuw; Paulus Kombo Allo Layuk; Andika Rante (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2019)
This study aims to determine: (1) The effect of financial management on the performance of local government, as well as (2) The effect of the financial accounting system on the performance of local government areas. This type of research is causative with the population were all working units (OPD) at Jayapura City, using 34 samples obtained with different educational backgrounds. The data collection method was used a questionnaire. By using multiple regression analysis tool such as SPSSversion 16. The result shows that: (1) financial management has a negative significant effect on the performance of local government, and (2) financial accounting system area has positive significant effect on the performance of local governments